Perancangan Aplikasi Skripsi Online Menggunakan Algoritma String Matching Knuth Morris-Pratt Pada Fakultas Teknik Universitas Islam Sumatera Utara - Arief Rahman Hakim; Khairuddin Nasution; Oris Krianto Sulaiman; Mhd. Zulfansyuri Siambaton (UIN Sumatera Utara, 2019)
This Online Thesis application aims to save a collection of theses at the Islamic University of North Sumatra in the form of electronic files and distributed so that they can be accessed and read online by visitors but cannot be copied files. This system has a facility to record user activities to find out visitor statistics, theses that are read frequently, browser statistics used by users and pages accessed by users, and has a fast search facility and detailed search for users. The article discusses how to design and implement Knuth Morris-Pratt String Matching Algorithm in the Online Thesis Application that is able to handle the storage of thesis files on the server in the form of Portable Document format (PDF) which is converted into Flipbook form using Turn Js as a tool in making flipbook display. This system was developed using PHP, MySql, and HTML5. The results obtained are a Web-based Online Thesis Application that features a flipbook that can help library management in managing digital theses, knowing which pages visitors are visiting, theses that are often read, and knowing visitor statistics. And can provide information about existing digital thesis and help library visitors in finding and reading digital thesis online. Keywords: thesis, flipbook, String Matching Knuth Morris-Pratt